Transformation of a living territory - Shahidan, Mohd Fairuz; Ujang, Norsidah; Hasna, Mohd Fabian (Universiti Putra Malaysia, 2012)
The concept of Transformation as a Living Territory is inspired by the term of flux. The design creatively plays with the flux movement and its flowing characteristic to link up the existing spaces and water bodies in order to congregate the ecological and human needs. The design also maximizes the appealing of outdoor spaces, turning them into a living territory. It forwards the concept of essential role of water in our living structure, whether visible or invisible. In this design, new community spaces that are clean, pleasant, bustling with life and activities are created for sustainable community. This design stresses on the importance of water supply infrastructure to ensure efficient water system and positively contributes to the social, cultural and recreational quality of urban living for long term benefits.